Efficient depolymerization and composite regeneration method of waste asphalt mixture
Patent Information
- Application Number
- CN202611118807.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-20
Abstract
Description
Technical Field
[0001] This invention belongs to the field of road engineering material recycling technology, specifically relating to an efficient depolymerization and composite recycling method for waste asphalt mixtures. Background Technology
[0002] With highway infrastructure entering a large-scale maintenance and renovation cycle, the amount of waste asphalt mixture generated is increasing dramatically. Its efficient and high-value recycling has become a key issue for the industry's sustainable development. Currently, plant-mixed hot recycling is the most widely used technology. Its core process involves forcibly mixing crushed and screened waste asphalt mixture with high-temperature new asphalt and new aggregates in a mixing drum.
[0003] However, this technology, which inherently relies on external heat conduction and mechanical shear force to disperse old materials and blend new and old materials, has several inherent drawbacks. The heat transfer process from the outside to the inside causes the asphalt on the surface of the old material to overheat and age easily, while the inside is difficult to soften sufficiently due to insufficient heat, resulting in a "half-cooked" phenomenon and low and incomplete deagglomeration efficiency. This necessitates the application of stronger shear forces during subsequent mechanical mixing, which not only consumes significant energy but also easily damages the edges of the aggregates, weakening the skeletal structure of the mixture.
[0004] Meanwhile, to ensure sufficient operating temperature, new asphalt and aggregates often need to be heated to higher temperatures, further accelerating the thermal aging of asphalt materials and impairing the long-term durability of recycled pavements. These factors collectively limit the increase of the amount of recycled materials in recycled mixtures, making it difficult to maximize resource utilization.
[0005] To address these issues, existing technologies have largely optimized traditional approaches, such as developing more penetrating recyclers, extending mixing time, or preheating the recycled material. However, these improvements either fail to overcome the fundamental limitations of traditional depolymerization methods relying on heat and force, or introduce new challenges such as higher energy consumption, more complex processes, or increased aging risks while solving old problems. Particularly for severely aged, high-asphalt-content fine-grained recycled materials, the extremely strong interfacial bonding has become a bottleneck that existing technologies struggle to effectively address. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a highly efficient depolymerization and composite recycling method for waste asphalt mixtures that is efficient, energy-saving, and thorough in depolymerization.
[0007] The technical solution adopted by this invention to solve its technical problem is: a method for efficient depolymerization and composite recycling of waste asphalt mixture, characterized by comprising the following steps: Pretreatment steps: The waste asphalt mixture is crushed and screened to obtain materials with different particle size ranges; The depolymerization process involves feeding materials of different particle size ranges into at least two independent depolymerization paths for processing, wherein: The first depolymerization path applies an electromagnetic energy field to materials within a first particle size range, transporting the materials within the first particle size range to the area affected by electromagnetic waves. By utilizing the difference in electromagnetic wave absorption capacity between asphalt and aggregates, the asphalt is selectively heated to soften it. The second depolymerization path involves applying a supercritical fluid field to materials within a second particle size range. This application of the supercritical fluid field includes placing the materials within the second particle size range in a pressure vessel containing supercritical fluid, allowing the supercritical fluid to penetrate the asphalt, and rapidly reducing the system pressure to cause the asphalt to expand in volume, thereby achieving separation from the aggregate. The average particle size of the materials within the second particle size range is smaller than the average particle size of the materials within the first particle size range. Collection and activation steps: The materials processed through the first and second depolymerization paths are collected and mixed with the regenerator for activation; Furthermore, the recycled mixture preparation steps are as follows: the activated material is mixed with at least one new aggregate or new asphalt to obtain a recycled asphalt mixture.
[0008] This invention provides a "classification, dual-path" synergistic depolymerization strategy. Compared to the "one-size-fits-all" thermo-mechanical depolymerization of existing technologies, this method achieves preliminary classification of materials through a pretreatment step, and then introduces coarse and fine materials with significantly different properties into two independent, highly adapted depolymerization paths. The first path utilizes the selective heating characteristics of electromagnetic energy to achieve rapid, efficient, and low-damage depolymerization of coarse materials; the second path utilizes the deep penetration and physical expansion of supercritical fluids to specifically target firmly bonded fine particles and powders that are difficult to handle by traditional methods. This "divide and conquer" strategy avoids the efficiency trade-offs and inherent contradictions of a single depolymerization method when processing complex materials, achieving a leap in overall depolymerization efficiency and thoroughness. Subsequent collection, activation, and mixing steps ensure that the fully depolymerized materials can be chemically activated and physically reconstructed to form a high-quality recycled mixture with uniform and stable properties.
[0009] Preferably, the frequency of the electromagnetic wave is 2.45 GHz; within the area of action of the electromagnetic wave, the passage time of the material is 3 s to 10 s, and the asphalt in the material is selectively heated to 120 ℃ to 150 ℃.
[0010] The electromagnetic wave frequency was limited to 2.45 GHz. Microwaves at this frequency have a highly efficient heating capability for polar substances like aged asphalt, with a moderate penetration depth. The material's transit time in the treatment area was controlled between 3 and 10 seconds, balancing efficiency and effectiveness. Too short a time would lead to uneven heating and incomplete depolymerization; too long a time would reduce processing capacity and damage asphalt properties due to overheating. This time range ensures that electromagnetic energy is effectively absorbed by the asphalt and converted into heat energy, achieving rapid softening. Limiting the target heating temperature of the asphalt to 120℃~150℃ has a dual advantage: firstly, this temperature is sufficient to significantly reduce the viscosity of aged asphalt to a range that is easy to flow and peel, meeting the process requirements for efficient depolymerization; secondly, it is significantly lower than the high temperatures of over 160℃ often reached in traditional thermal recycling, thereby maximally suppressing secondary thermal aging of the asphalt during the depolymerization process, protecting the original performance potential of the asphalt, and reserving more space for subsequent activation.
[0011] Preferably, the supercritical fluid is supercritical carbon dioxide; the conditions for depolymerization using the supercritical fluid include: a temperature of 55℃~80℃, a pressure of 8MPa~16MPa, and a processing time of 20min~40min; the rapid reduction of system pressure means reducing the pressure to atmospheric pressure within 5s.
[0012] Supercritical carbon dioxide was chosen as the working fluid because its critical conditions of 31.1℃ and 7.38MPa are mild, easy to achieve and maintain; simultaneously, CO2 is chemically stable, non-toxic, non-flammable, inexpensive, and recyclable. Setting the temperature between 55℃ and 80℃ and the pressure between 8MPa and 16MPa ensures that CO2 is in a superior supercritical state, possessing high density, high diffusion coefficient, and moderate solubility, effectively penetrating the micropores and interfaces of aged asphalt. A processing time of 20-40 minutes ensures sufficient time for supercritical CO2 to achieve deep penetration and swelling equilibrium in the fine materials. Most importantly, the depressurization process is completed within 5 seconds. This rapid depressurization is achieved through a large-diameter pneumatic ball valve (DN50, opening time <0.5s), with the pressure relief port connected to the condensation recovery system, achieving a CO2 recovery rate of ≥95%. Rapid pressure reduction causes a large amount of CO2 dissolved in asphalt to instantly reach a supersaturated state, which then escapes rapidly and generates a huge micro-expansion force. This force can "expand" and "tear" the asphalt film from the inside, thus achieving complete stripping with minimal external mechanical force.
[0013] Preferably, in the second depolymerization path, a surfactant is added to the supercritical fluid, wherein the amount of surfactant added is 0.1% to 0.5% of the mass of the material in the second particle size range.
[0014] This invention, based on supercritical CO2 depolymerization, introduces synergistic additives. A trace amount of surfactant is added to reduce the interfacial tension between supercritical CO2 and aged asphalt / aggregate, improving the wettability, spreadability, and penetration rate of CO2 in complex porous asphalt systems. This helps supercritical CO2 reach the asphalt-aggregate interface more quickly and uniformly, shortening the time required to achieve the desired depolymerization effect and improving processing efficiency.
[0015] More preferably, the surfactant is a bio-based surfactant. Compared to traditional petroleum-based synthetic surfactants, the use of bio-based surfactants offers significant advantages in terms of sustainability and environmental friendliness. First, their raw materials are derived from renewable biomass. Second, these surfactants possess good biodegradability, resulting in less environmental impact and higher ecological safety in later stages of the process or throughout the product lifecycle.
[0016] Further preferably, the bio-based surfactant is at least one of lecithin, sucrose ester, or sorbitan ester. Lecithin is a natural amphoteric surfactant with good emulsifying and wetting properties, effectively promoting interfacial interactions between the nonpolar phase of asphalt and the aggregate surface or the polar phase of CO2. Sucrose ester and sorbitan ester are nonionic surfactants derived from the esterification of natural sugars and fatty acids. They are safe, non-toxic, and biodegradable, and their hydrophilic-lipophilic balance (HLB) value can be flexibly adjusted by the degree of esterification to meet the interfacial characteristic requirements of asphalt at different aging stages. These three substances were specifically chosen because they have been widely used in the food, cosmetics, and other fields, their safety has been fully verified, and their production and application technologies are mature. In the supercritical CO2 environment of this invention, they can effectively function, enhancing the depolymerization effect while ensuring the environmental friendliness of the entire regeneration process.
[0017] Specifically, in the pretreatment step, the waste asphalt mixture is separated into materials with a first particle size range of 4.75mm to 35mm and materials with a second particle size range of 0 to 4.75mm by screening.
[0018] Using 4.75mm (corresponding to a 5mm sieve aperture in a standard sieve) as the aperture for the grading sieve has a solid engineering foundation. Typically, materials with particle sizes larger than 4.75mm are mainly coarse aggregates with relatively thin asphalt films on their surfaces. Furthermore, the aggregates themselves have weak electromagnetic wave absorption, making them ideally suited for electromagnetically targeted flash heating deagglomeration to achieve rapid, efficient, and shape-preserving deagglomeration. Materials with particle sizes no larger than 4.75mm contain fine aggregates and enriched recycled mineral powders. They have a large specific surface area, severe asphalt aging, and strong interfacial adhesion, making deagglomeration challenging. This makes them well-suited for the supercritical fluid deagglomeration path, which requires deep penetration and a gentle yet thorough process. This grading standard is clear, easily implemented in industrial settings using a standard vibrating sieve, ensuring the accuracy and repeatability of the classification.
[0019] Preferably, the regenerator is an activating regenerator, which comprises a coated fast-penetrating component and a performance-restoring component.
[0020] Traditional regenerators are simple physical mixtures of multiple components. Upon addition, all components act simultaneously, leading to inefficiency due to the incomplete penetration preceding the modification process. The activated regenerator of this invention uses encapsulation technology to physically separate functionally distinct "rapid-penetrating components" and "performance-restoring components," achieving a programmed and sequential release of functions. During the activation phase, the encapsulation structure is first broken or opened, releasing the rapid-penetrating component. This component quickly wets and swells the depolymerized but not yet fully dispersed aged asphalt, reducing system viscosity and promoting initial intermingling of new and old asphalt, creating favorable conditions for subsequent reactions. Subsequently, the performance-restoring component is released, dispersing more evenly and effectively in the softened asphalt environment to achieve toughening, reinforcement, and molecular-level repair. This "penetration-first, repair-second" logic significantly improves the utilization efficiency and overall repair effect of the regenerator.
[0021] More preferably, the activating regenerator has a microcapsule structure, and the wall material of the microcapsule is at least one of hydrogenated vegetable oil, paraffin wax, or polyethylene wax; the core material of the microcapsule is the rapid penetration component and the performance repair component, the rapid penetration component contains light oil, and the performance repair component is a polymer modifier; the polymer modifier includes styrene-butadiene-styrene block copolymer (SBS).
[0022] Microcapsules are an ideal carrier for controlled release. Hydrogenated vegetable oils, paraffin wax, or polyethylene wax are chosen for the wall material because these materials have well-defined and adjustable melting points, allowing them to be precisely designed to melt near a subsequent activation temperature of 120°C to 150°C. This achieves a temperature-triggered "switch" release effect, ensuring precise release of the core material when needed. In the core material, light oils act as penetrants, rapidly softening and diluting aged asphalt. SBS is the preferred polymer modifier, significantly improving the high-temperature rutting resistance, low-temperature cracking resistance, and elastic recovery of recycled asphalt.
[0023] Optionally, the polymer modifier may also include polymers with dynamic covalent bonds. Introducing polymers containing dynamic covalent bonds endows recycled asphalt mixtures with potential self-healing capabilities. At microcracks generated during pavement service, under stress or temperature triggering, the dynamic covalent bonds can undergo reversible breakage and recombination, achieving autonomous healing of microcracks and significantly extending the fatigue life of the pavement. This is an advanced function that traditional recycling technologies cannot achieve.
[0024] Preferably, the mixing activation in the collection and activation step is carried out at 120℃~150℃, causing the coating structure to melt and sequentially release the rapid-penetrating component and the performance-repairing component. This temperature range ensures that the microcapsule wall material can completely melt, thereby smoothly releasing the core material functional components, which is a physical prerequisite for triggering sequential release. Secondly, this temperature is significantly lower than the mixing temperature of 160℃~180℃ for new and old asphalt in traditional thermal recycling, thus effectively avoiding additional thermal oxidation damage to the asphalt during the activation stage. At the same time, this temperature is sufficient to ensure that the asphalt has good fluidity, which is conducive to the full contact, diffusion and reaction between the recycling agent components and the depolymerized asphalt, ensuring uniform and thorough activation. This relatively mild activation temperature, matched with the front-end low-temperature / medium-temperature depolymerization process, together constitute a green recycling process with low temperature and medium aging throughout the process, which maximizes the protection of the material's essence and reduces energy consumption and emissions while ensuring high-performance recycling.
[0025] This invention relates to a method for recycling waste asphalt. In implementing this method, commonly used equipment in the field can be selected and assembled according to process requirements. For example, the following is a multi-mode deep depolymerization and recycling system for waste asphalt mixtures that can implement the above method, comprising: a pretreatment device for crushing and screening the waste asphalt mixture; a first depolymerization device, which constitutes a first depolymerization path for applying a first energy field to materials within a first particle size range; a second depolymerization device, which constitutes a second depolymerization path independent of the first depolymerization path for applying a second energy field to materials within a second particle size range, wherein the average particle size of the materials within the second particle size range is smaller than the average particle size of the materials within the first particle size range; a collection and activation device for receiving and mixing materials from the first and second depolymerization devices and adding a recycling agent; and a mixing device for mixing the materials from the collection and activation device with at least one new aggregate or new asphalt.
[0026] This system transforms the traditional single, sequential processing flow into an integrated system encompassing pretreatment, dual-path parallel depolymerization, intelligent aggregation and activation, and final mixing. This achieves a "divide and conquer" and "parallel optimization" of the process. Through independent "first depolymerization unit" and "second depolymerization unit," the system can simultaneously operate two depolymerization processes, handling materials with vastly different properties without interference and with synergistic efficiency, significantly improving overall processing capacity and flexibility.
[0027] Preferably, the first depolymerization device is a continuous microwave or radio frequency depolymerization device, including a resonant cavity and a material transfer mechanism; the second depolymerization device is an intermittent or continuous supercritical fluid processing device, including a pressure-resistant reactor, a pressure and temperature control system, and a fluid recovery and circulation device.
[0028] Compared with existing technologies, the beneficial effects of this invention are as follows: This invention effectively overcomes the drawbacks of traditional thermo-mechanical depolymerization methods, such as incomplete depolymerization, high energy consumption, and easy damage to aggregates, through a synergistic depolymerization strategy of "categorization and dual-pathway". For coarse-grained materials, electromagnetic targeted flash heating depolymerization is used, achieving selective and rapid softening of asphalt with high efficiency and avoiding thermal damage to aggregates and secondary aging of asphalt. For difficult-to-handle fine-grained and highly aged materials, supercritical CO2 fluid deep penetration and rapid pressure reduction physical stripping are used to achieve gentle and thorough depolymerization. Combined with the programmed release of intelligent activating regenerators, the performance repair effect of aged asphalt and the fusion quality of new and old materials are significantly improved. The entire method significantly improves depolymerization efficiency and the performance of recycled mixtures while achieving low-temperature and green processes throughout, providing a reliable technical solution for high-proportion, high-value recycling of waste asphalt mixtures. Detailed Implementation
[0029] The present invention will be further described below with reference to specific embodiments, wherein Embodiment 1 is the basic embodiment, and the process conditions not specified in other embodiments and comparative examples are the same as in Embodiment 1. The embodiments take the treatment of waste asphalt mixture as an example to specifically illustrate the implementation process of the efficient depolymerization and composite recycling method of the present invention. For ease of process comparison, the waste asphalt mixture (RAP) used in the following embodiments and comparative examples are all taken from the surface layer milled material of a highway, and are used after crushing and screening to remove oversized particles. The macroscopic properties and composition of this batch of RAP are as follows: the asphalt-aggregate ratio is 4.8% (i.e., the asphalt content is about 4.58%), the penetration of the recycled aged asphalt (25℃, 100g, 5s) is 28 (0.1mm), the softening point (ring and ball method) is 68.5℃, and the ductility (15℃) is 12cm. The aggregate gradation conforms to the AC-20 discontinuous gradation, of which coarse aggregate above 4.75mm accounts for about 62%, and fine aggregate and mineral powder below 4.75mm accounts for about 38%. All embodiments and comparative examples used the same batch of RAP to ensure objectivity of the comparison. This invention also applies to RAPs with other performance characteristics. Example 1
[0030] First, pretreatment is performed. One ton of blocky RAP from the maintenance site is fed into a jaw crusher for primary crushing, and then sieved through a 31.5mm and a 4.75mm square-hole screen. After sieving, two grades of material are obtained: one grade is coarse-grained RAP with a particle size range of 4.75mm~35mm, weighing approximately 650kg; the other grade is fine-grained RAP with a particle size no larger than 4.75mm, containing recycled mineral powder rich in asphalt, weighing approximately 350kg. Both grades of material are then subjected to hot air drying to control their moisture content to below 3%. The coarse-grained material is preheated to approximately 80℃ to remove moisture, while the fine-grained material is dried at room temperature for subsequent use.
[0031] Subsequently, the core deagglomeration stage begins. Approximately 650 kg of preheated coarse-grained RAP is uniformly and continuously fed into a continuous microwave deagglomeration device via a feeder. The device's resonant cavity operates at a frequency of 2.45 GHz, and the microwave power is adjusted according to the throughput to ensure a material transit time of approximately 7 seconds within the cavity. During this process, microwave energy is selectively absorbed by the aged asphalt in the RAP, causing its temperature to rapidly rise to approximately 135°C within seconds and fully soften, while the internal aggregate temperature rise is minimal. The material then falls into a low-speed rotating vortex loosening chamber. This vortex loosening chamber is a conical cylinder with rotating scrapers at the bottom rotating at 10-30 rpm. Under the influence of centrifugal force and gravity, the material spirals down the cylinder wall, and the softened asphalt film is effectively peeled off from the aggregate surface through gravity and gentle impact. Simultaneously, approximately 350 kg of fine-grained RAP is fed into an intermittent supercritical fluid processing system. After the materials are loaded into the pressure-resistant reactor, liquid food-grade CO2 is injected into the system. The system is then heated and pressurized through a jacket to reach and maintain a supercritical state at 65°C and 12 MPa. This state is maintained for 30 minutes, during which lecithin (0.3% of the mass of fine-particle RAP) is injected into the supercritical CO2 as a surfactant. After the maintenance phase, the system pressure is rapidly reduced to atmospheric pressure within 5 seconds using a back pressure valve. This sudden pressure drop causes the CO2 dissolved in the asphalt to escape rapidly, creating a "micro-explosion" effect that expands and tears the tightly bound asphalt film from the inside. Finally, gentle mechanical stirring completes the dissociation. The dissociated CO2 is then condensed, recovered, and recycled.
[0032] After depolymerization, the materials are collected and activated. The materials from the two aforementioned pathways, having achieved basic separation of asphalt and aggregate, are jointly transported to an activation tank equipped with heating and stirring functions. The tank temperature is controlled at 130℃. An activation regenerating agent is sprayed into the material, with an addition amount accounting for 6% of the total mass of the original aged asphalt in the RAP. This regenerating agent is in microcapsule form, prepared as follows: 100 parts of paraffin wax with a melting point of 125℃ are heated to 130℃ and melted, 30 parts of naphthenic oil and 10 parts of SBS are added, and the mixture is emulsified by high-speed stirring at 3000 rpm for 5 minutes. The emulsion is then dripped into cold water at 5℃ to solidify, filtered, and dried to obtain microcapsules with a particle size of 50~200μm. The core material encapsulation rate is ≥85%. At the activation temperature of 130℃, the microcapsule wall material melts, and the core material is released in the order of "oil first, then adhesive": naphthenic oil first impregnates and dilutes the depolymerized aged asphalt, followed by uniform dispersion of SBS for reinforcement and modification. This activation process lasts for 5 minutes to ensure that the new and old asphalt components are fully integrated and their properties are restored.
[0033] Finally, the recycled asphalt mixture is prepared. All activated materials (a mixture of recycled binder and recycled aggregate) are transferred to a standard asphalt mixing plant. Based on the target gradation (AC-20) and asphalt-aggregate ratio, approximately 200 kg of fresh limestone aggregate preheated to 155°C and approximately 15% of the total asphalt content, heated to 160°C, are added to the mixing drum. Simultaneously, 2.5% of the total asphalt mass of Lufite high-viscosity asphalt modifier is added. Mixing is carried out at approximately 150°C, first dry mixing for 8 seconds, then adding the asphalt and warm mix agent and wet mixing for 40 seconds. After thorough mixing, the mixture is discharged, yielding a high-performance recycled asphalt mixture with a temperature of approximately 145°C. Example 2
[0034] The process was essentially the same as in Example 1, except that: 1 ton of blocky RAP was taken, crushed, and sieved using a 4.75mm square-hole sieve to obtain approximately 600 kg of coarse-grained RAP and approximately 400 kg of fine-grained RAP. The coarse-grained RAP, after drying and preheating, was fed into a continuous microwave depolymerization device. To ensure the lower limit of the test parameters, the microwave power was adjusted to a low level, controlling the material's passage time in the resonant cavity precisely to 3 seconds, and infrared monitoring was used to ensure the asphalt phase temperature in the material reached exactly 120°C. After this brief and rapid targeted heating, the asphalt was initially softened and then dissociated in the vortex chamber. The fine-grained RAP underwent deep depolymerization using supercritical CO2, with process parameters set at 60°C, 10 MPa, and 25 min, followed by rapid depressurization within 5 seconds after completion. The two materials were then combined, and a regenerator composed of a physical mixture of light naphthenic oil and a small amount of SBS was directly added at 5% of the old asphalt mass. Activation and mixing were carried out at a low temperature of 125°C for 4 minutes. Finally, the recycled mixture is warm-mixed with new aggregates and new asphalt at approximately 145°C to obtain the recycled mixture. Example 3
[0035] The process is essentially the same as in Example 1, except that 1.2 tons of blocky RAP was processed, and approximately 400 kg of coarse material and 800 kg of fine material were obtained through sieving. The coarse material was subjected to electromagnetic depolymerization, with the asphalt heated to 140°C for 6 seconds. For the fine material, fine-grained RAP was added to a supercritical reactor at a set temperature of 80°C and a pressure of 16 MPa (the upper limit of the process pressure). During the 30-minute processing, 0.5% (by weight of the fine material) of sucrose ester was added to the supercritical CO2 as a bio-based surfactant. The pressure was rapidly released after processing. After collecting the materials, a regenerator was added. The microcapsule wall material was polyethylene wax (melting point approximately 130°C), and the core material contained light oil and SBS, added at a rate of 7%. Mixing and activation were carried out at an activation temperature of 150°C for 5 minutes to ensure the wall material melted and the functional components were released sequentially. The final regeneration mixing temperature was controlled at 155°C. Example 4
[0036] The process is essentially the same as in Example 1, except that 1 ton of blocky RAP is crushed and sieved through a 31.5 mm and a 4.75 mm square-hole sieve. Approximately 670 kg of coarse material and 330 kg of fine material are obtained. The coarse material enters the electromagnetic depolymerization path, but the conveying speed is adjusted to heat the asphalt within the coarse material to approximately 145°C to accommodate its different thermal conductivity characteristics. The fine material undergoes supercritical CO2 depolymerization with parameters set at 70°C, 12 MPa, and 35 min, without the addition of surfactants. After depressurization and depolymerization, the material is collected, and a microcapsule regenerator with hydrogenated vegetable oil as the wall material is added and activated at 135°C. Example 5
[0037] The process is essentially the same as in Example 1, except that: 2.2t of blocky RAP was crushed and sieved to obtain 1.5t of coarse material and 0.7t of fine material. Electromagnetic depolymerization of the coarse material was performed using high power to raise the asphalt temperature to 150°C for 8 seconds to ensure thorough softening. Supercritical depolymerization of the fine material was performed at 75°C, 14MPa, and 40 minutes, with the addition of 0.4% sorbitol ester. After depolymerization, the materials were collected, and the amount of active regenerator added was 8% of the mass of the old asphalt. The activation process was carried out at 150°C for 6 minutes. Example 6
[0038] The process was essentially the same as in Example 1, except that approximately 0.8 t of RAP was used, and sieved to obtain 500 kg of coarse material and 300 kg of fine material. The coarse material underwent electromagnetic depolymerization, with the asphalt temperature controlled at 140°C for 5 seconds. The fine material underwent supercritical CO2 depolymerization at a set temperature of 65°C, a pressure of 12 MPa, and a processing time of 30 minutes. During this process, 0.2% (by weight of the fine material) of lecithin was added to the system as a bio-based surfactant. After depolymerization, the materials were collected, and an active regenerator was added. The wall material of the active regenerator microcapsules was paraffin wax, and the core material, besides light oils, consisted of SBS as its performance-restoring component. The active regenerator was added at 6.5% of the old asphalt mass. Activation mixing was carried out at 135°C for 5 minutes. The final mixing temperature of the recycled mixture was 150°C. Example 7
[0039] The process was essentially the same as in Example 1, except that 1.5t of RAP was processed, yielding approximately 1t of coarse material and 0.5t of fine material after sieving. The coarse material underwent electromagnetic depolymerization at an industry-standard 2.45GHz frequency, stabilizing the asphalt temperature at 130℃. The material passed through the resonant cavity for 6 seconds, achieving a good balance between efficiency and energy consumption. The supercritical depolymerization parameters for the fine material were set at 70℃, 12MPa, and 30min, without the addition of surfactants. After aggregation, an active regenerator was added, with hydrogenated vegetable oil as the microcapsule wall material (melting point 118℃) and naphthenic oil and SBS as the core material. The active regenerator dosage was 5.5%. At an activation temperature of 130℃, the hydrogenated vegetable oil wall material melted, enabling controlled release of the core material, with an activation time of 4min. Finally, warm mixing was performed at 148℃. Example 8
[0040] The process was essentially the same as in Example 1, except that: 1 ton of RAP was deeply crushed and sieved through a 4.75 mm sieve to obtain approximately 200 kg of coarse aggregate and 800 kg of fine aggregate. The coarse aggregate underwent electromagnetic depolymerization, with the asphalt temperature controlled at 135°C for 7 seconds. For the fine aggregate, a higher supercritical pressure of 15 MPa was used, with the temperature controlled at 75°C and the treatment time extended to 40 minutes to ensure the deep action of supercritical CO2 on the high specific surface area fine powder. Simultaneously, 0.4% (by weight of the fine aggregate) of sorbitol ester was added as a bio-based surfactant to enhance penetration. After rapid depressurization, due to the extremely high fine aggregate content and large total amount of aged asphalt, the amount of active recycling agent added was increased to 7.5% of the old asphalt mass. The activation temperature was set at 145°C and maintained for 6 minutes to ensure full integration. Finally, the RAP content in the recycled mixture reached 85% during mixing.
[0041] Comparative Example 1 The process is essentially the same as in Example 1, except that 1 ton of RAP material from the same source and in the same quantity as in Example 1 is used. This material is simply crushed to a maximum particle size of no more than 31.5 mm, but without fine sieving or grading. All the RAP material and fresh aggregate are fed into the drying drum of a standard plant-mixed hot recycling equipment and directly heated using a gas flame. The new aggregate is heated to a high temperature of 155°C. Subsequently, the high-temperature RAP, new aggregate, and new asphalt are heated to above 175°C and then fed into the mixing drum. Strong mechanical shearing and mixing are performed for 75 seconds using high-speed rotating blades within the drum, forcibly separating and dispersing the RAP clumps through mechanical force. The discharge temperature after mixing is approximately 165°C. Observation revealed that the final mixture contained visible, incompletely dispersed RAP clumps, indicating incomplete deagglomeration. Extraction and sieving of the finished mixture showed large fluctuations in gradation, and the penetration of the recovered asphalt was significantly lower than the design value, confirming severe thermal aging.
[0042] Comparative Example 2 The process was essentially the same as in Example 1, except that processing 1 t of RAP also yielded approximately 650 kg of coarse material and 350 kg of fine material. All materials were processed using the electromagnetic targeted flash thermal depolymerization path described in Example 1. While the coarse material effectively depolymerized during passage through the microwave resonant cavity, the fine particles, due to their large specific surface area and rapid heat transfer, could not be heated to their effective softening temperature within the same passage time. This resulted in a significant amount of fine material failing to depolymerize and existing as powdery agglomerates, severely impacting subsequent activation and the uniformity of the final mixture.
[0043] Comparative Example 3 The process was essentially the same as in Example 1, except that processing 1 t of RAP also yielded approximately 650 kg of coarse aggregate and 350 kg of fine aggregate. All materials were processed using only the supercritical fluid deep depolymerization pathway. All materials were fed into the reactor and treated at 65°C and 12 MPa for 30 minutes. The results showed that while the fine aggregate depolymerization was effective, a large amount of coarse aggregate occupied the effective volume of the reactor. Furthermore, its large volume and center of mass rendered the supercritical fluid's penetration effect insufficient for peeling off the thin asphalt film from the coarse aggregate surface, resulting in extremely low energy efficiency, high unit processing costs, and lack of economic viability.
[0044] In practical industrial applications, to address the time mismatch between the first depolymerization path (continuous microwave depolymerization) and the second depolymerization path (intermittent supercritical CO2 depolymerization), the following solutions can be adopted: Multiple (e.g., 3-4) supercritical reactors are set up, and the alternating feeding, processing, unloading, and cleaning cycles are realized through PLC controllers. Taking the parameters of Example 1 as an example, the processing cycle of a single reactor is 35 minutes (including loading, heating and pressurizing, holding for 30 minutes, rapid depressurization, and unloading). If 3 reactors are equipped, each reactor will start a cycle at an interval of about 11.7 minutes, which can match the fine material processing capacity with the coarse material continuous microwave equipment (processing capacity of about 5.6 t / h).
[0045] The above solution can achieve capacity matching between the two depolymerization processes, ensuring continuous and stable operation of the production line. Those skilled in the art can flexibly choose the solution based on site, investment scale, and processing capacity.
[0046] To uniformly verify the implementation effects of each embodiment and comparative example, the following performance tests were conducted. The test methods followed the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011). Dynamic stability (DS) was tested using the rutting test (60℃, 0.7MPa); the water immersion Marshall residual stability ratio (MS0) was the ratio of the water immersion time of 48 hours to the standard Marshall stability; the freeze-thaw splitting strength ratio (TSR) was the ratio of the splitting strength after one freeze-thaw cycle to the splitting strength of the unfrozen specimen. Specific performance parameters are shown in Table 1 below.
[0047] Table 1 Performance verification results of recycled asphalt mixtures in each embodiment and comparative example .
[0048] The high-temperature stability (DS) and water stability (MSO, TSR) of Examples 1-8 of this invention are significantly better than those of the comparative examples. This verifies the synergistic effect of the dual-pathway depolymerization of coarse asphalt using "electromagnetic targeted flash heating" and "supercritical fluid deep depolymerization of fine asphalt," combined with the technical advantages of programmed release of the regenerating agent. This allows for efficient, low-temperature depolymerization while maximally protecting and restoring asphalt properties, thereby producing high-performance recycled mixtures. Comparative Example 1 exhibits the lowest performance. While the single depolymerization pathway performance of Comparative Examples 2 and 3 is better than that of Comparative Example 1, it is significantly lower than that of any of the embodiments of this invention.
[0049] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A method for efficient depolymerization and composite recycling of waste asphalt mixtures, characterized in that, Includes the following steps: Pretreatment steps: The waste asphalt mixture is crushed and screened to obtain materials with different particle size ranges; The depolymerization process involves feeding materials of different particle size ranges into at least two independent depolymerization paths for processing, wherein: The first depolymerization path applies an electromagnetic energy field to materials within a first particle size range, transporting the materials within the first particle size range to the area affected by electromagnetic waves. By utilizing the difference in electromagnetic wave absorption capacity between asphalt and aggregates, the asphalt is selectively heated to soften it. The second depolymerization path involves applying a supercritical fluid field to materials within a second particle size range. This application of the supercritical fluid field includes placing the materials within the second particle size range in a pressure vessel containing supercritical fluid, allowing the supercritical fluid to penetrate the asphalt, and rapidly reducing the system pressure to cause the asphalt to expand in volume, thereby achieving separation from the aggregate. The average particle size of the materials within the second particle size range is smaller than the average particle size of the materials within the first particle size range. Collection and activation steps: The materials processed through the first and second depolymerization paths are collected and mixed with the regenerator for activation; Furthermore, the recycled mixture preparation steps are as follows: the activated material is mixed with at least one new aggregate or new asphalt to obtain a recycled asphalt mixture.
2. The method for efficient depolymerization and composite recycling of waste asphalt mixture according to claim 1, characterized in that, The frequency of the electromagnetic wave is 2.45 GHz; within the area affected by the electromagnetic wave, the passage time of the material is 3 s to 10 s, and the asphalt in the material is selectively heated to 120 ℃ to 150 ℃.
3. The method for efficient depolymerization and composite recycling of waste asphalt mixture according to claim 1, characterized in that, The supercritical fluid is supercritical carbon dioxide; the conditions for depolymerization using supercritical fluid in the second depolymerization path include: temperature of 55℃~80℃, pressure of 8MPa~16MPa, and processing time of 20min~40min; the rapid reduction of system pressure means reducing the pressure to atmospheric pressure within 5s.
4. The method for efficient depolymerization and composite recycling of waste asphalt mixture according to claim 3, characterized in that, In the second depolymerization path, a surfactant is added to the supercritical fluid, wherein the amount of surfactant added is 0.1% to 0.5% of the mass of the material in the second particle size range.
5. The method for efficient depolymerization and composite recycling of waste asphalt mixture according to claim 4, characterized in that, The surfactant is a bio-based surfactant.
6. The method for efficient depolymerization and composite recycling of waste asphalt mixture according to claim 5, characterized in that, The bio-based surfactant is at least one of lecithin, sucrose ester, or sorbitol ester.
7. The method for efficient depolymerization and composite recycling of waste asphalt mixture according to claim 1, characterized in that, In the pretreatment step, the waste asphalt mixture is separated into materials with a first particle size range of 4.75mm to 35mm and materials with a second particle size range of 0 to 4.75mm by screening.
8. The method for efficient depolymerization and composite recycling of waste asphalt mixture according to claim 1, characterized in that, The regenerant is an activating regenerant, which contains a coated fast-penetrating component and a performance-restoring component.
9. The method for efficient depolymerization and composite recycling of waste asphalt mixture according to claim 8, characterized in that, The activating regenerator has a microcapsule structure, and the wall material of the microcapsule is at least one of hydrogenated vegetable oil, paraffin wax, or polyethylene wax; the core material of the microcapsule is the rapid penetration component and the performance repair component, the rapid penetration component contains light oil, and the performance repair component is a polymer modifier; the polymer modifier includes styrene-butadiene-styrene block copolymer.
10. The method for efficient depolymerization and composite recycling of waste asphalt mixture according to claim 1, characterized in that, The mixing and activation in the collection and activation steps is carried out at 120℃~150℃.